Physician antibiotic hydration preferences for biologic antibacterial envelopes during cardiac implantable device procedures - Deering, Thomas F.; Catanzaro, John N.; Woodard, David A. (Frontiers in Cardiovascular Medicine, 2022)
Background Cardiac implantable electronic device (CIED) infection is a potentially serious complication of CIED procedures. Infection risk mitigation includes using guideline recommended pre-operative intravenous antibacterial prophylaxis (IV ABX). The use of antibiotic eluting CIED envelopes has also been shown to reduce infection risk. The relationship between, and potential benefits associated with guideline recommended IV ABX in combination with antibacterial envelopes have not been characterized. Methods Biologic envelopes made from non-crosslinked extracellular matrix (ECM) were implanted into 1,102 patients receiving CIEDs. The implanting physician decided patient selection for using a biologic envelope and envelope hydration solution. Observational data was analyzed on IV ABX utilization rates, antibacterial envelope usage, and infection outcomes. Results Overall compliance with IV ABX was 96.6%, and most patients received a biologic envelope hydrated in antibiotics (77.1%). After a mean follow up of 223 days, infection rates were higher for sites using IV ABX <80% of the time vs. sites using ≥80% (5.6% vs. 0.8%, p=.008). Physicians demonstrated preference for hydration solutions containing gentamicin in higher-risk patients, which was found by multivariate analysis to be associated with a 3-fold reduction in infection risk (OR 3.0, 95% CI, 1.0 – 10.0). Conclusions These findings suggest that use of antibiotics, particularly gentamicin, in biologic envelope hydration solution may reduce infection risk, and use of antibacterial envelopes without adjunct IV ABX may not be sufficient to reduce CIED infections.